Children’s Fan-Play, Folklore and Participatory Culture: Harry Potter Costumes, Role-Play and Spells - Small, Contessa (Ethnologies, 2016)
The study of children’s play activities has not only been historically trivialized, but numerous widely held misconceptions about kids, their play, folklore and popular culture continue to persist today despite evidence to the contrary. For example, some adults believe that mass media and popular culture has contributed to the decline of kids’ traditional play activities, while others argue that traditional play objects are being replaced by “media culture artifacts”; however, the child-centred fan-play research I present in this paper reveals that popular culture encourages and activates children’s traditional and creative competences, rather than destroy them. The Harry Potter “phenomenon”, as a contested site where youth struggle for visibility and power, serves as the case study for this paper. Based on ethnographic observation of several local events, surveys, and interviews with child and teenage fans of Harry Potter, I examine several emergent, participatory, fan-play activities (including costuming, role-playing, make-believe and spells) and discuss the many ways children manipulate, appropriate, adapt and combine popular culture and folklore, using both creativity and tradition as expression of their lives, identities and power struggles. I conclude by discussing the heart of contemporary children’s culture and play – the conservative/creative nature of children, hybrid play forms and the activation of traditional and creative competencies in the face of popular culture influences.